Contribution of RaeB, a Putative RND-Type Transporter to Aminoglycoside and Detergent Resistance in Riemerella anatipestifer - Zhang, Xin; Wang, Ming-Shu; Liu, Ma-Feng; Zhu, De-Kang; Biville, Francis; Jia, Ren-Yong; Chen, Shun; Sun, Kun-Feng; Yang, Qiao; Wu, Ying; Zhao, Xin-Xin; Chen, Xiao-Yue; et al. (Frontiers in Microbiology, 2017)
Riemerella anatipestifer is an important pathogenic bacterium that infects ducks. It exhibits resistance to multiple classes of antibiotics. Multidrug efflux pumps play a major role as a mechanism of antimicrobial resistance in Gram-negative pathogens and they are poorly understood in R. anatipestifer. In this study, a gene encoding the B739_0873 protein in R. anatipestifer CH-1, which belongs to the resistance-nodulation-cell division (RND) efflux pump family, was identified. With respect to the substrate specificity of B739_0873, the antibiotic susceptibility testing showed that the B739_0873 knockout strain was more sensitive to aminoglycosides and detergents than the wild-type strain. The transcription of B739_0873 was up-regulated when R. anatipestifer CH-1 was exposed to sub-inhibitory levels of these substrates. From the gentamicin accumulation assay, we concluded that B739_0873 was coupled to the proton motive force to pump out gentamicin. Furthermore, site-directed mutagenesis demonstrated that Asp 400, Asp 401, Lys 929, Arg 959 and Thr 966 were the crucial function sites of B739_0873 in terms of its ability to extrude aminoglycosides and detergents. Finally, we provided evidence that B739_0873 is co-transcribed with B739_0872, and that both B739_0872 and B739_0873 are required for aminoglycoside and detergent resistance. In view of these results, we designate B739_0873 as RaeB (Riemerella anatipestifer efflux).